2010
DOI: 10.1007/s12015-010-9115-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Disassembly and Cell Rounding Promotes Adipogenesis from ES Cells

Abstract: Biomechanical signals such as cell shape and spreading play an important role in controlling stem cell commitment. Cell shape, adhesion and spreading are also affected by calreticulin, a multifunctional calcium-binding protein, which influences several cellular processes, including adipogenesis. Here we show that cytoskeletal disruption in mouse embryonic stem cells using cytochalasin D or nocodazole promotes adipogenesis. While cytochalasin D disrupts stress fibres and inhibits focal adhesion formation, nocod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 83 publications
(126 reference statements)
4
35
0
1
Order By: Relevance
“…[47][48][49][50] An examination of cytoskeletal dynamics in NC9-treated preadipocytes plated on FN under serum-free conditions showed that the inhibitor dramatically reduced actin stress fiber formation and increased cortical actin assembly compared with control cells. This was also associated with reduced focal adhesion assembly as seen by a lack of vinculin colocalization with actin stress fibers ( Figure 4A).…”
Section: Fxiii-a Activity Promotes Actin Dynamics and Focal Adhesion mentioning
confidence: 99%
“…[47][48][49][50] An examination of cytoskeletal dynamics in NC9-treated preadipocytes plated on FN under serum-free conditions showed that the inhibitor dramatically reduced actin stress fiber formation and increased cortical actin assembly compared with control cells. This was also associated with reduced focal adhesion assembly as seen by a lack of vinculin colocalization with actin stress fibers ( Figure 4A).…”
Section: Fxiii-a Activity Promotes Actin Dynamics and Focal Adhesion mentioning
confidence: 99%
“…This response is mediated by modulation of focal adhesion length and myosin II activity (Engler et al, 2006). The finding that disruption of cytoskeletal structures manipulated cell morphology and specifically directed the cells towards an adipogenic fate (Feng et al, 2010) also supports an involvement of cytoskeletal tension in regulation of hES cell differentiation state. Besides externally imposed mechanical cues like matrix stiffness also cyclic biaxial strain affects the differentiation state of hES cells (Saha et al, 2006).…”
Section: Wwwintechopencommentioning
confidence: 70%
“…Our work highlights the important effects of defined micro-topography on ES-cell-colony formation and morphology. Since cell shape (Feng et al, 2010) and colony morphology (Lee et al, 2009) are linked to ES-cell differentiation, topography offers an extra level of possibilities for directing ES-cell fate through modulation of cell and colony morphology. Furthermore, the BSSA approach has been applied to other cell types as well, thereby facilitating immediate comparison between cell types over the same topographical patterns and ranges produced in the same material (Kolind et al, 2010;Lovmand et al, 2009).…”
Section: Self-renewal and Differentiationmentioning
confidence: 99%
“…23,24 In addition, disrupting cytoskeleton or decreasing cell rigidity reduces the expression of osteoblastic gene, including alkaline phosphatase (ALP) and osteopontin, 25,26 and further promotes adipogenic differentiation by increasing peroxisome proliferator-activated receptor (PPAR) gamma. 18,20,27 The cytoskeletal organization and myosin-mediated cytoskeleton tension are regulated by RhoA and its effector, Rho-associated protein kinase (ROCK). Activation of RhoA causes human MSCs to undergo osteogenic differentiation by upregulating the expression of Runx2 gene; however, inactivation of RhoA causes cells to undergo adipogenic differentiation by increasing expression of the adipogenic marker gene PPAR gamma.…”
Section: Tai Et Almentioning
confidence: 99%